2001
DOI: 10.1046/j.1365-2141.2001.03118.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in vitro fertilization treatment and subsequent pregnancy on the protein C pathway

Abstract: Summary. Thirty-three women who were planned for an in vitro fertilization (IVF) cycle donated blood at four time points during treatment: at baseline, after downregulation, hyperstimulation and luteal support. Levels of progesterone, 17b-oestradiol and indicators of the protein C pathway, i.e. activated protein C sensitivity ratios (APCsr), protein C, protein C inhibitor and protein S were measured. Compared with baseline, oestradiol decreased twofold at downregulation and increased 40-fold at hyperstimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 36 publications
3
20
1
1
Order By: Relevance
“…These ®ndings agree with preliminary studies in women treated with hMG or r-hFSH, showing that ovarian stimulation does not cause APC resistance (Biron et al, 1997;Wramsby et al, 2000). However, recently, other authors, using a different test to evaluate APC resistance, Rosing's test (Rosing et al, 1999;Tans et al, 2003), observed a signi®cant increase in APC sensitivity ratio during r-hFSH administration, and concluded that acquired APC resistance occurred in women undergoing ovarian stimulation (Curvers et al, 2001). These discordant results might be because the APC resistance test used in the latter study had a higher sensitivity to hormonal changes.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…These ®ndings agree with preliminary studies in women treated with hMG or r-hFSH, showing that ovarian stimulation does not cause APC resistance (Biron et al, 1997;Wramsby et al, 2000). However, recently, other authors, using a different test to evaluate APC resistance, Rosing's test (Rosing et al, 1999;Tans et al, 2003), observed a signi®cant increase in APC sensitivity ratio during r-hFSH administration, and concluded that acquired APC resistance occurred in women undergoing ovarian stimulation (Curvers et al, 2001). These discordant results might be because the APC resistance test used in the latter study had a higher sensitivity to hormonal changes.…”
Section: Discussionsupporting
confidence: 75%
“…Other authors (Biron et al, 1997) using GnRH analogue and hMG reported a signi®cant decrease before hCG administration and no changes during the luteal phase, although pre-treatment assessment was not performed. The results of a more recent study (Curvers et al, 2001) seem to suggest a different effect of r-hFSH compared to u-hFSH. Indeed, in women stimulated with rhFSH, a slight increase in Protein C activity at down-regulation and during the other phases of treatment was reported.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the present study, resistance to APC was measured with an assay that is particularly sensitive to changes in the hormonal status of women, 12,16,24,27,28 ie, with a test that quantifies the effect of APC on thrombin generation initiated via the extrinsic coagulation pathway (endogenous thrombin potential-based test). 21 nAPCsr determined with this test correlates remarkably well with the risk increase of venous thromboembolism reported in oral contraceptive users and in carriers of the factor V Leiden mutation.…”
Section: Post Et Al Estrogen Replacement Therapy and Resistance To Apcmentioning
confidence: 99%
“…Total protein S 22 and free protein S 23 were determined by ELISA. Protein C activity, 24 prothrombin, 25 and C-reactive protein 20 were measured as described before. We used C-reactive protein concentrations to test whether the pathways that mediate estradiolassociated increases in C-reactive protein are similar to those that mediate estradiol-associated changes in hemostatic variables.…”
Section: Assaysmentioning
confidence: 99%